2021
DOI: 10.1111/bld.12370
|View full text |Cite
|
Sign up to set email alerts
|

Lost voices part 2: Modifying psychological therapies for two young men with complex learning disabilities following alleged sexual and physical abuse: A case study in trauma recovery

Abstract: Accessible summary Two young men who have learning disabilities became mentally ill. They said that they had been hurt by their carers. They said that the carers hit them and made them have sex with them. They had post‐traumatic stress disorder, which made them scream, cry, hurt themselves and have frightening nightmares. They were helped by a Mental Health of Learning Disabilities Team. They talked to a psychologist which helped them to understand what happened to them. Talking to the psychologist helped th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This review also did not include the considerable number of narratively described individual case studies, which reported no quantitative or qualitative outcome data (e.g. Hill‐Weld 2011; Digman 2021). These may nevertheless be informative illustrations of the application of family‐systems interventions with families of people with an ID or who are autistic (although they would not add strength to any conclusions about their effectiveness).…”
Section: Discussionmentioning
confidence: 99%
“…This review also did not include the considerable number of narratively described individual case studies, which reported no quantitative or qualitative outcome data (e.g. Hill‐Weld 2011; Digman 2021). These may nevertheless be informative illustrations of the application of family‐systems interventions with families of people with an ID or who are autistic (although they would not add strength to any conclusions about their effectiveness).…”
Section: Discussionmentioning
confidence: 99%